Effect of Capital Structure, Firm Size and Leverage on Firm Value with Profitability as an Intervening Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange - Sihombing, Lasminar; Astuty, Widia; Irfan, Irfan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine and analyze effect of capital structure, firm size and leverage on firm value with profitability as an intervening variable in Manufacturing Companies listed on the Indonesia Stock Exchange. Capital structure is measured by debt to equity ratio. Profitability is measured by return on assets. Firm value is measured by price to book value. This research uses associative approach method. The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange. While the samples taken were 64 companies using purposive sampling. To obtain the data needed in this study, the authors use documentation techniques from data published by the company on the Indonesia Stock Exchange official website www.idx.co.id, as well as the company's annual report. The data used in this study is quantitative data sourced from secondary data. The research technique uses data analysis (path analysis) and the tool is the SmartPLS version 3.0 program. The results of this study indicate that: (1)Debt to equity ratio has no effect on price to book value. (2)Firm size has no effect on price to book value. (3)Leverage has no effect on price to book value. (4)Debt to equity ratio has an effect on return on assets. (5)Firm size has an effect on return on assets. (6)Leverage has an effect on return on assets. (7)Debt to equity ratio has no effect on price to book value through return on assets. (8)Firm size has no effect on price to book value through return on assets. (9)Leverage has no effect on price to book value through return on assets.